tanθ+β =pi/4, show that (1+tanθ)(1+tan )=2
tanֿ¹(1/2) = α tanֿ¹(1/3) = β α + β = θ tanθ = tan(α + β) = [tanα + tanβ] / [1 - tanαtanβ] = [(1/2) + (1/3)] / [1 - (1/2)(1/3)] = [3 + 2] / [6 - 1] = 1 Angles α and β are both acute, so α + β < π, θ < π. This means θ must be in quadrant 1 or 2. tanθ = 1 θ = π/4 α + β = π/4 tanֿ¹(1/2) + tanֿ¹(1/3) = π/4
so from above we know that
tanθ = 1 by putting
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?